Interviews in Healthcare: A Phenomenological Approach A Qualitative Research Methodology - Tanwir, Farzeen; Moideen, Sarah; Habib, Raiya (Journal of Public Health International, 2021)
Phenomenology is a ritual of Qualitative research methodology. Interviews in healthcare enables researchers to recognise and understand data from lived experiences of the participants by using Phenomenological approach. The purpose of this article is to review the various face to face in depth interviews conducted using Husserl’s descriptive, Heidegger’s interpretive phenomenology or Hermeneutic phenomenological approach in healthcare. The in-depth interview will help to understand the health issues and ethical issues faced by participants. Methodology Four articles were selected based on phenomenological approach. Article.1 was based on Hermeneutic Phenomenology approach. In this study thirteen women were taken as sample. Sampling was done by snowball method. The women were asked to share their rural maternity experience. Data was analyzed without any influence of the researcher. Article.2 was based on Transcendental phenomenology. There were 15 students from 4 different cultural background belonging to different health professional programmes like nursing, medicine, pharmacy, dentistry, and physical therapy. Triangulation methods were used and semi structured interviews were conducted, recorded and transcribed. Health professional students shared their lived experience with patients. Article.3 was based on a study conducted using both Transcendental phenomenology for patients interviews and Hermeneutic phenomenology for healthcare professionals’ interviews. The semi structured interview of patient was taken to understand and record their lived experience with the medication without any bias or interpretation and data received was bracketed. The healthcare professionals’ interviews were conducted on Hermeneutic strategy regarding the medications they prescribe for life threatening illnesses. Article 4 was based on Hermeneutic phenomenological approach. There were nine patients selected and in depth semi-structured interviews were conducted. The patients shared their experience of living with a life limiting illness.
Keywords: Phenomenology; Research; Qualitative research; Hermeneutic phenomenology